Emergency medical equipment on board German airliners - Hinkelbein, Jochen; Neuhaus, Christopher; Wetsch, Wolfgang A.; Spelten, Oliver; Picker, Susanne; Böttiger, Bernd W.; Gathof, Birgit S. (Journal of travel medicine, 2014)
AbstractBackground. Medical emergencies often occur on commercial airline flights, but valid data on their causes and consequences are rare. Therefore, it is
Published 06 June 2014
Gesehen am 16.09.2020